Health-Risk Behaviours in Emerging Adults: Examining the Relationships among Personality, Peer, and Parent Variables - Blum, Cheryl (Université d'Ottawa / University of Ottawa, 2012)
College students and emerging adults have been found to be at risk for smoking cigarettes, drinking to excess, using illicit drugs, driving dangerously, and engaging in risky sexual and delinquent behaviour. Psychosocial correlates (Sensation Seeking, peer behaviour, parent behaviour, and peer and parent anti-substance use messages) from three domains of influence (personality, parent, and peer) were examined together to provide a greater context for the occurrence of such health-risk behaviours. The strongest predictor(s) of each behaviour were identified to better inform intervention practices. Three groups were compared— 1) those who never tried substances, 2) those who tried substances in the past, and 3) those who continue to use substances at present, in a population of emerging adults. Self-report data was gathered from 203 Collèges d'Enseignement Général Et Professionnel (CEGEP) students in the Montreal region. Measures included: Reckless Behaviour Questionnaire, Reckless Driving Measure, Health Behaviour Survey, Sensation Seeking Scale—Form V, and the Marlowe-Crowne Social Desirability Scale. Results revealed that peer behaviour was the most significant predictor of substance use in emerging adults, whereas parent behaviour was only a significant predictor of reckless driving. Sensation Seeking, specifically Disinhibition, was found to predict more global reckless behaviours, including illegal activities, such as stealing or using marijuana (p < .01). Neither peer nor parent anti-substance messages were significantly related to any of the health-risk behaviours measured in this study. It would appear that health-risk behaviours tend to be related to the same underlying factors but to varying degrees. Intervention implications are discussed.
Keywords: health-risk behaviours; reckless behavior; emerging adulthood; emerging adults; cigarette smoking; alcohol inebriation; marijuana usage; risky behaviour; Sensation Seeking; drunk